THE IMPACT OF SOCIAL MEDIA AND THE LACK OF KNOWLEDGE ABOUT REPRODUCTIVE HEALTH ON SEXUAL BEHAVIOR IN EARLY ADOLESCENTS - Nurhayati Nurhayati; Alya Alfianti Balqis; Risca Muril Khairani; Delfi Yunita Lubis; Laila Sari (Jurnal Scientia, 2023)
In Indonesia, many young people have premarital sex, meaning they have sex before marriage. This happens to around 15-20% of teenagers. During adolescence, which is the period when children are growing up, teenagers often don't know their bodies enough and make mistakes because it is easy to find information on the internet and social media. This community service seeks to educate teens about the impact of social media on their health and how to make better choices regarding sex. This counseling is intended for Medan Al-Kahfi Foundation Middle School students and will use various activities such as watching video and discussions.